Evaluation of physical condition for the 2016 Summer Olympics in Rio de Janeiro using both internal and external load in Under23 Japan National Football Team - Nakamura, D.; Nakamura, M.; Hayakawa, N. (Journal of High Performance Sport, 2019)
This study aimed to evaluate the physical conditions of the U23 Japan National Football Team during the 2016 Summer Olympics football tournament in Rio de Janeiro and before the preparation camp. Both internal factors (internal load: IL) and external factors (external load: EL) were evaluated during this period. IL was evaluated by resting heart rate, body weight, visual analog scale (including subjective fatigue quality of sleep, appetite, etc.,), salivary cortisol levels, secretory immunoglobulin A (SIgA) levels, and EL was evaluated by GPS data during training and game in this period. The results of this study showed that body weight, heart rate on awakening, and salivary IgA levels changed on the day of after a game, as well as increasing subjective fatigue scales. The GPS data showed that the physical load between players was different when they performed the same practice. However, despite of the decrease in EL, there was a case where physical condition evaluated by IL deteriorated. In conclusion, the combined evaluation of IL and EL may help determine training load and evaluate the conditions of elite soccer players during the pre-camp and following major football tournament.